2010
DOI: 10.1021/ma1013012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Study onp-Quinodimethane Formation in the Sulfinyl Precursor Route for the Polymerization of Poly(p-phenylenevinylene) (PPV)

Abstract: The kinetics of p-quinodimethane formation in the sulfinyl precursor route for the poly-(p-phenylenevinylene) (PPV) polymerization was studied using stop-flow UV-vis spectroscopy and theoretical first principle calculations. Different sulfinyl monomers were studied by means of quantitative kinetic experiments regarding the p-quinodimethane formation in 2-butanol. The influence of the solvent, the nature of the aromatic moiety, and the substituents on the phenyl core was analyzed by means of qualitative experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…In accordance with the observations reported by Hermosilla et al, 51 no indication for polymerization was found during the kinetic runs in this work and the only products absorbing in the UVÀvis spectrum are the premonomer (HML), the p-quinodimethane monomer (M) and the ether byproduct (P 1 ). The maximum of the UVÀvis absorbance of the pquinodimethane is situated around a wavelength of 313 nm, 51,77 which is also the wavelength used in the UVÀvis experiments in this study to monitor the p-quinodimethane. As indicated by Hermosilla et al, 51 the contributions to the absorbance at 313 nm of the premonomer and the substitution product P 1 can be neglected.…”
Section: ' Experimental Proceduressupporting
confidence: 93%
“…In accordance with the observations reported by Hermosilla et al, 51 no indication for polymerization was found during the kinetic runs in this work and the only products absorbing in the UVÀvis spectrum are the premonomer (HML), the p-quinodimethane monomer (M) and the ether byproduct (P 1 ). The maximum of the UVÀvis absorbance of the pquinodimethane is situated around a wavelength of 313 nm, 51,77 which is also the wavelength used in the UVÀvis experiments in this study to monitor the p-quinodimethane. As indicated by Hermosilla et al, 51 the contributions to the absorbance at 313 nm of the premonomer and the substitution product P 1 can be neglected.…”
Section: ' Experimental Proceduressupporting
confidence: 93%
“…[55] 6 -311 + + G(3df,3pd) extra basis set was used for the sulfur atoms to attain more accurate results. [37,56,57] In order to evaluate the activation barriers accurately energy refinements were performed with hybrid-GGA MPW1 K [58,59] range-separated CAMÀ B3LYP [60] and double hybrid B2PLYP [61] functionals. Table 1 displays Gibbs free energies of activation (ΔG � ) and reaction (ΔG rxn ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic reaction coordinate (IRC) [55,56] paths were traced to find the two associated minima directly connected to each transition state (TS) on the potential-energy surfaces. The BMK [57] functional, particularly developed for kinetics and well-known for its good performance in both radical and nucleophilic substitution reactions, [19,25,27,39,58] was employed in conjunction with the 6-311 + GA C H T U N G T R E N N U N G (3df,2p) basis set to further refine energies of B3LYP optimized structures. The BMK/6-311 + G-A C H T U N G T R E N N U N G (3df,2p)//B3LYP/6-31 + GA C H T U N G T R E N N U N G (d,p) level of theory was recently shown to effectively reproduce experimental heats of formation and thermochemical data in reactions of organophosphorus compounds and derived radicals.…”
Section: Methodsmentioning
confidence: 99%